Case Report: Identification of a De novo C19orf12 Variant in a Patient With Mitochondrial Membrane Protein–Associated Neurodegeneration - Yang, Yue; Zhang, Shijie; Yang, Wenming; Wei, Taohua; Hao, Wenjie; Cheng, Ting; Wang, Jiuxiang; Dong, Wei; Qian, Nannan (Frontiers in Genetics, 2022)
Background: Mitochondrial membrane protein-associated neurodegeneration (MPAN) mostly arises as an autosomal recessive disease and is caused by variants in the chromosome 19 open reading frame 12 (C19orf12) gene. However, a few C19orf12 monoallelic truncating de novo variants have been reported and segregated as autosomal dominant traits in some cases. Methods: We performed whole-exome sequencing and analyzed genes related to neurodegeneration associated with brain iron accumulation for pathogenic variants. The identified variants were confirmed by Sanger sequencing and tested using in silico tools. Results: The patient had an onset of depression at age of 22 years, which rapidly progressed to severe dystonia, dementia, and bladder and bowel incontinence. Neuroimaging showed hypointensity in the substantia nigra and the globus pallidum, with additional frontotemporal atrophy. Genetic analysis revealed a single complex de novo variant [c.336_338delinsCACA (p.Trp112CysfsTer40)] in the C19orf12 gene. Conclusions: This study enriches the genetic spectrum and clinical features of C19orf12 variants and provides additional evidence of the variable inheritance pattern of MPAN.